2021
DOI: 10.3389/fbinf.2021.695784
|View full text |Cite
|
Sign up to set email alerts
|

Short Tandem Repeats as a High-Resolution Marker for Capturing Recent Orangutan Population Evolution

Abstract: The genus Pongo is ideal to study population genetics adaptation, given its remarkable phenotypic divergence and the highly contrasting environmental conditions it’s been exposed to. Studying its genetic variation bears the promise to reveal a motion picture of these great apes’ evolutionary and adaptive history, and also helps us expand our knowledge of the patterns of adaptation and evolution. In this work, we advance the understanding of the genetic variation among wild orangutans through a genome-wide stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Polymorphic STRs were also found to allow for better identification of pig breeds in comparison to SNPs. Another study in wild orangutan populations identified distinct STR length changes in genes linked to species' recent local adaptations, such as increased brain size and reproductivity (Voicu et al, 2021 ).…”
Section: Phenotypic Diversity Created By Strs With...mentioning
confidence: 99%
“…Polymorphic STRs were also found to allow for better identification of pig breeds in comparison to SNPs. Another study in wild orangutan populations identified distinct STR length changes in genes linked to species' recent local adaptations, such as increased brain size and reproductivity (Voicu et al, 2021 ).…”
Section: Phenotypic Diversity Created By Strs With...mentioning
confidence: 99%
“…Microsatellites or short tandem repeats, consisting of tandem repeats of motifs up to 6 bp in length, are prevalent in both prokaryotic and eukaryotic genomes. Some microsatellites have been shown to be functionally important ( Kashi and King 2006 ; Mirkin 2007 ; Gemayel et al 2010 ), but most are assumed to evolve neutrally, and for this reason, along with their abundance and high variability, they have been used extensively in population genetics studies ( Schlötterer 2004 ; Voicu et al 2021 ; Shi et al 2023 ). While there have recently been important advances in our understanding of their genomic distribution ( Srivastava et al 2019 ) and evolutionary dynamics ( Jonika et al 2020 ; Verbiest et al 2022 ), it remains unclear whether microsatellite loci are in dynamic equilibrium with respect to the length of alleles or whether alleles experience directional drift in length.…”
Section: Introductionmentioning
confidence: 99%